The use of nanostructured films in sensing applications - Riul, Antonio; Miyazaki, Celina Massumi [UNESP]; Dantas, Cléber A. R. [UNESP]; Oliveira, Osvaldo N. (My University, 2013)
In this chapter, we describe developments on the use of impedance spectroscopy and ultrathin films of different materials in the analysis of liquid samples via weak, non-bonding molecular interactions. Despite the lack of intrinsic selectivity in many cases, the simplicity of the sensor is quite attractive and enhanced by the nanostructured thin nature of the materials forming the sensing units. Moreover, it is possible to incorporate materials capable of molecular recognition, such as enzymes, extending the e-tongue concept to biosensing. Advantage can also be taken from the supramolecular interactions between the ultrathin films and the liquid samples under analysis, and integration of sensing units in microarrays for high-performance, high-throughput sensors.